Imagining the east: the early theosophical society - Rudbøg, Tim; Reenberg Sand, Erik (Oxford University Press, 2020)
The essays in Imagining the East explore how Theosophists during the formative period imagined the religions and cultures of the East. The authors examine the relationship of such representations to orientalism, the history of ideas, politics, and culture at large and discuss how these esoteric or theosophical representations mirrored conditions and values current in nineteenth-century mainstream intellectual culture. The essays also look at how the early Theosophical Society's representations of the East differed from mainstream 'orientalism' and how the Theosophical Society's mission in India was distinct from that of British colonialism and Christian missionaries.
Description based on publisher supplied metadata and other sources
Keywords: Geschichte; Theosophie; The Theosophical Society